Real-time pricing and the cost of clean power - Imelda Imelda; Matthias Fripp; Michael J. Roberts (Graduate Institute of International and Development Studies, 2022)
Solar and wind power are now cheaper than fossil fuels but are intermittent. The extra supply-side variability implies growing benefits of using real-time retail pricing (RTP). We evaluate the potential gains of RTP using a model that jointly solves investment, supply, storage, and demand to obtain a chronologically detailed dynamic equilibrium for the island of Oahu, Hawai'i. Across a wide range of cost and demand assumptions, we find the gains from RTP in high-renewable systems to exceed those in a conventional fossil system by roughly 6 times to 12 times, markedly lowering the cost of renewable energy integration.
Keywords: Q41; Q42; Q53; 330; Renewable energy; real-time pricing; storage; demand response; optimization